2006
DOI: 10.1038/sj.cdd.4402025
|View full text |Cite
|
Sign up to set email alerts
|

Elucidation of some Bax conformational changes through crystallization of an antibody–peptide complex

Abstract: The Bcl-2 family member Bax plays a critical role in apoptosis. In healthy resting cells, Bax resides in the cytoplasm and loosely attached to the mitochondrial membrane. Apoptotic stimuli induce Bax activation, which is characterized by translocation and multimerization on the mitochondrial membrane surface resulting in exposure of an amino terminal epitope recognized by the monoclonal antibody 6A7. To understand the structural changes that occur during Bax activation, we determined the crystal structure of a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
39
0

Year Published

2009
2009
2017
2017

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 50 publications
(40 citation statements)
references
References 38 publications
1
39
0
Order By: Relevance
“…Moreover, the epitopes are in the region of Bax a1 (residues 13-19, 1-21 and 11-30, respectively) that abuts the a6-a8 latch domain [34][35][36] , and the epitopes of polyclonal Bax N20 may even include residues of the Bax BH4 domain ( 26 LLQGFI 31 ). As Bax N-terminal exposure is akin to that for Bak, a1 dissociation is probably also required for Bax activation and pore formation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, the epitopes are in the region of Bax a1 (residues 13-19, 1-21 and 11-30, respectively) that abuts the a6-a8 latch domain [34][35][36] , and the epitopes of polyclonal Bax N20 may even include residues of the Bax BH4 domain ( 26 LLQGFI 31 ). As Bax N-terminal exposure is akin to that for Bak, a1 dissociation is probably also required for Bax activation and pore formation.…”
Section: Discussionmentioning
confidence: 99%
“…1a). For three of these antibodies , the immunogen contained a stretch of residues (26)(27)(28)(29)(30)(31)(32)(33)(34)(35)(36) conserved in mouse and human Bak (Table 1). Another two antibodies (4B5 and G23) had previously been mapped to a conserved region 9 .…”
Section: Most Bak Antibodies Have Linear Epitopesmentioning
confidence: 99%
“…17 This was evidenced by confocal immunofluorescence analysis using the conformation-specific 6A7 Bax-antibody (Figure 2a) raised against the NH 2 -terminal epitope of the Bax protein, which is exposed on 'full' Bax activation. 7,18 In all individual cells analysed, YFP-Bax activation (as evidenced by the 6A7 antibody and detected in the red channel, Alexa 594) was associated with a significant clustering of YFP-Bax fluorescence detected in the YFP channel. Similar results were obtained in DU145-Bax cells expressing untagged Bax (Figure 2a; Supplementary Figure 1a).…”
Section: Resultsmentioning
confidence: 99%
“…51 On a different note, one should consider that Bax has an essential, non-apoptotic, homeostatic activity, since it can associate with mitochondria under normal conditions, regulating mitochondrial energy production. 25,26 Indeed, cells deficient in Bax display decreased mitochondrial oxidative capacity and reduced levels of intracellular ATP. 26 These observations would be consistent with the weak or absent mitochondrial-dependent production of ROS in HCT116 Bax -/-.…”
Section: Discussionmentioning
confidence: 99%
“…24 Recently it has been also shown that Bax plays a role in mitochondrial energy production, where its deficiency leads to decreased mitochondrial oxidative capacity and reduced levels of intracellular ATP. 25,26 Also, cysteine residues in Bax can chemically react with ROS, leading to a change in its conformation and subsequent activation. 25,27,28 In this study, using HCT116 Bax +/-and HCT116 Bax -/-cells, 29 we show that PGC1α overexpression induces Bax translocation to mitochondria with a consequent release of cyt c and …”
Section: Pgc1α Induces Bax Activationmentioning
confidence: 99%